1972
DOI: 10.1677/joe.0.0540215
|View full text |Cite
|
Sign up to set email alerts
|

ACTION OF OESTRADIOL-17β AND CYCLIC AMP ON THE SYNTHESIS OF RNA, PHOSPHOPROTEINS AND PHOSPHOLIPIDS IN THE UTERUS OF OVARIECTOMIZED RATS IN VITRO

Abstract: Administration of oestradiol-17\g=b\ to ovariectomized rats increases the incorporation of [32P]orthophosphate into RNA, phosphoproteins and phospholipids of the uterus. Uteri taken from the ovariectomized rats pretreated with oestradiol for 1 h in vivo continued to manifest enhanced ability to incorporate 32P into RNA, phospholipids and phosphoproteins when tested in vitro. However, when oestradiol was added directly to the incubation medium, it failed to stimulate to the same extent the incorporation of [32P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

1973
1973
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 20 publications
0
2
1
Order By: Relevance
“…Possibly the best indication of this functional interdependence is provided by studies on the anucleolate mutant of Xenopus laevis, where synthesis of both rRNA and polyamines is virtually absent (Russell, 1971). Our failure to stimulate RNA synthesis with cyclic AMP is at variance with previous reports on other steroid-sensitive systems, such as rat uterus (Sharma & Talwar, 1970;Rao & Talwar, 1972). It should be emphasized, however, that the selection of radioactive precursor (Miller & Baggett, 1972) and large changes in the pools of nucleotides (Oliver & Kellie, 1970;Greenman, 1970Greenman, , 1971 are known to influence dramatically the incorporation of radioactive precursors into uterine RNA during whole-tissue incubations.…”
Section: Discussioncontrasting
confidence: 88%
“…Possibly the best indication of this functional interdependence is provided by studies on the anucleolate mutant of Xenopus laevis, where synthesis of both rRNA and polyamines is virtually absent (Russell, 1971). Our failure to stimulate RNA synthesis with cyclic AMP is at variance with previous reports on other steroid-sensitive systems, such as rat uterus (Sharma & Talwar, 1970;Rao & Talwar, 1972). It should be emphasized, however, that the selection of radioactive precursor (Miller & Baggett, 1972) and large changes in the pools of nucleotides (Oliver & Kellie, 1970;Greenman, 1970Greenman, , 1971 are known to influence dramatically the incorporation of radioactive precursors into uterine RNA during whole-tissue incubations.…”
Section: Discussioncontrasting
confidence: 88%
“…Studies were mainly on gamete physiology and regulation of gametogenesis and fertility control measures in terms of promoting or inhibiting fertilization using rodents (Raj and Moudgal, 1970;Gaur and Talwar, 1975;Talwar et al, 1979) and non-human primate models (Moudgal et al, 1971;Anand Kumar et al, 1980. Experimental approaches involved gonadectomy models (Rao and Talwar, 1972;Lohiya and Dixit, 1974), reproductive endocrinology (Mukku and Moudgal, 1970;Singh et al, 1971), in vitro culture of reproductive tissues and their derived cell types (Talwar and Sharma, 1975;Paul et al, 1978) and reproductive toxicological studies (Kar et al, 1967). Besides, work was also carried out on screening of Indian plants for antifertility effect (Satyavati, 1984) and on endocrine disruptors (Batra, 1966).…”
Section: Gamete Development and Functionmentioning
confidence: 99%
“…injection of diethylstilboestrol into ovariectomized rats. Furthermore, Hechter, Yoshinaga, Halkerston & Birchall (1967) showed that exo¬ genous cyclic AMP mimicked the anabolic effects of oestradiol on the rat uterus in vitro with respect to RNA, protein, lipid and glycogen synthesis (see also Sharma & Talwar, 1970;Rao & Talwar, 1972;Singhal & Lafreniere, 1972) and Griffin & Szego (1968) obtained stimulation of uterine amino acid uptake in vitro by cyclic AMP.…”
Section: Introductionmentioning
confidence: 94%